Gender differences in unemployment insurance coverage: A comparative analysis - Janine Leschke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Social insurance systems are known to reproduce gender inequalities in the labour market because they are usually based on 'standard employment contracts' (full-time, permanent, dependent) and often take into account the household constellation through means-testing. Gender inequalities in the labour market consist of higher part-time employment rates, more frequent movements between employment and inactivity and on average lower wages among women. These inequalities are mainly due to the unequal distribution of household and family tasks between men and women. This paper will use the data of the European Household Panel to compare access to and level of unemployment benefits between men and women. Differences in access to benefits are usually brought about by the following design features of unemployment benefits: hours and earnings thresholds, minimum contribution requirements, and means-testing, whereas the benefit levels in many systems are calculated as a share of former earnings, and among long-term unemployed are also affected by means-testing. – – Da soziale Sicherungssysteme auf sogenannte Normalarbeitsverhältnisse (Vollzeit, unbefristet, abhängig) ausgerichtet sind und häufig von Bedarfsprüfungen Gebrauch machen, reproduzieren sie Geschlechterungleichheiten im Arbeitsmarkt, die auf Grund der ungleichen Verteilung von Haushalts- und Familienaufgaben zwischen Frauen und Männern zustande kommen. So sind Frauen beispielsweise weit häufiger in Teilzeit beschäftigt, sie wechseln häufiger zwischen Beschäftigung und Inaktivität und verdienen weiterhin durchschnittlich geringere Löhne als Männer. Das Papier vergleicht auf Basis der Daten des Europäischen Haushaltspanels den Deckungsgrad und die Höhe von Arbeitslosenversicherungsleistungen zwischen Frauen und Männern. Unterschiede im Zugang zu Arbeitslosenversicherungsleistungen werden unter anderem durch die folgenden Charakteristika von Arbeitslosenversicherungssystemen bestimmt: Einkommens- oder Stundenschwellenwerte, Mindestbeitragszeiten und Bedarfsprüfungen. Die Höhe der Leistungen hängt in vielen Systemen von der Höhe der vormaligen Arbeitseinkommen ab, wird aber bei Langzeitarbeitslosen häufig auch durch Bedarfsprüfungen bestimmt.
Keywords: 330; Geschlechterdiskriminierung; Arbeitslosenversicherung; Deutschland; Dänemark; Spanien; Großbritannien